Estimation of economic equations as a management tool in feedlot dairy farming - Sousa, Flávio Vieira de; Santana Junior, Hermógenes Almeida; Santana, Elizângela Oliveira Cardoso; Mendes, Fabrício Bacelar Lima; Souza, Breno Silva e; Silva, Alice Bernardo da (Acta Scientiarum. Animal Sciences, 2024)
The aim of this study was to evaluate Pearson’s linear correlations between productive and economic indicators as well as to estimate economic equations as tools in dairy farming. We used the database of the Research Group, registered with CNPq under the title ‘Animal and Forage Production in Piaui’, which consisted of two experiments with feedlot lactating cows. Economic and productive indicators were employed. Correlations were determined by Pearson’s linear correlation analysis, using the ‘t’ test. Equations were estimated via regression, using Saeg software (Statistical and Genetic Analysis System), considering α = 0.05. Based on concepts related to Pearson’s linear correlation and dairy farming management, we were able to find correlations that allowed us to estimate simple, yet very informative equations, which facilitated the interpretation of the management of a dairy farm. Among the studied variables, net present value, internal rate of return, the cost per liter of milk produced and net margin were those which most contributed to the estimation of equations.